Resilience in the face of adversity: psychological adaptation in a psychogerontological program for grief care - Ortiz Hernández, Arantxa (2023)
In old age, losing a loved one can be one of the most stressful events a person might experience. After the loss, the survivor faces a process of personal and social changes that requires an expenditure of internal and external resources and the strengthening of their support network. The study aimed to measure the state of resilience in older people after a psychogerontological intervention for grief care. A pre-test and post-test were administered to six participants in a grief care intervention using the Mexican Resilience Scale (RESI-M). The results indicate that there was an improvement in their overall resilience levels after the intervention, as well as an individual increase in specific resilience factors. Implementing interventions that promote the ability to adapt to adverse situations can be a valuable option for improving the quality of life of the elderly population.